Karl Popper’s Solution to the Problem of Induction and the Non-Justificationist Conception of Rationality - Sepetyi, Dmytro (Actual Problems of Mind, 2021)
The article provides a detailed account and elucidation of Karl Popper’s solution to Hume’s problem of induction. It is pointed out that the solution has two major aspects. The first, explicitly described by Popper as his solution to the problem of induction, is the replacement of the inductivist account of the development of empirical knowledge, according to which cognition begins with observations of particular events and proceeds through inductive inferences to certainly true or highly probable theories-generalisations, with the hypothetico-deductivist account, according to which cognition begins with a problem and proceeds through conjecturing its possible solutions (advancing hypotheses) and attempts to falsify them by reproducible results of observations/experiments. The second aspect has to do with the problem of justification of the hypothetico-deductivist account (which replaces Hume’s problem of the justification of induction). This problem is shown to be dealt with within Popper’s-Bartley’s general solution to the problem of justification, usually described as «non-justificationism», which admits the impossibility of absolute definitive justification (for any position) and replaces the search for such justification with the evaluation of relative advantages/disadvantages of competing approaches, which can provide us with reasons to prefer or tentatively accept one of them. The comparison is made between Popper’s hypotheticodeductivist account and Charles Pierce’s account based on abduction, or inference to the best explanation. It is shown that these accounts has similar logical structures, that with respect to empirical science they suggest mutual corrections and clarifications, and that inference to the best explanation can provide justification for the assumption of the existence of laws of nature, which is implicit in the hypothetico-deductivist account.